Changes in microstructure and mechanical properties of 2219 Al alloy during hot extrusion and post-extrusion aging - Shengxiang Wan; Heng Su; Bin Shao; Yingying Zong; Debin Shan; Bin Guo (Journal of Materials Research and Technology, 2023)
2219 Al alloy is widely used in the aerospace industry owing to its outstanding properties. In this study, we evaluated the effects of the extrusion temperature and extrusion ratio on the microstructure and mechanical properties of extruded 2219 Al alloy specimens, including the changes during post-extrusion aging. In the extrusion temperature range of 380–500 °C, the mechanical properties of the bar after extrusion at 470 °C were the best. Furthermore, extrusion ratios up to 25:1 produced extruded rods with excellent mechanical properties and microstructure. Increasing the extrusion temperature increased the dissolution of the eutectic θ phase in the solid solution and accelerated the breakage of the inclusions contained Mn/Fe. Some larger and coarse as-cast grains were mechanically fractured during hot extrusion, with the fragments then rotated towards directions with high Schmid factors, thus forming banded dynamic recrystallization regions. The grain boundaries of the recrystallized grains were predominantly low-angle boundaries. The 2219 Al alloy aged at 170 °C for 16 h produced the densest and most uniform distribution of needle-like nanoscale θ′ phase inside the grains, resulting in an average hardness of 149 HV. Further increasing the aging time and temperature resulted in the aggregation and growth of θ′ phase precipitates.